Legal protection for MSMEs in digital trade regulation in Indonesia: A study of aspects of intellectual property rights, business competition, and consumer protection - Pramana, Yorie F (Institute Of computer Science (IOCS), 2025)
The development of digital trade in Indonesia presents significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to grow but also poses substantial challenges in legal protection. MSMEs face issues such as weak protection of intellectual property rights (IPR), unhealthy business competition, and inadequate consumer protection. This phenomenon highlights the need for an in-depth analysis of existing regulations and their implementation in the context of digital trade. This study employs a normative juridical method with a statute approach and case approach to analyze relevant regulations, such as Law No. 28 of 2014 on Copyright, Law No. 5 of 1999 on Prohibition of Monopolistic Practices, and Law No. 8 of 1999 on Consumer Protection. The findings reveal that although the regulations provide a sufficient legal framework, their implementation is hindered by the lack of MSME awareness, complex administrative processes, and weak oversight. The results of this research recommend that the government simplify procedures, improving legal and digital literacy, and strengthening oversight to create an inclusive and sustainable digital trade ecosystem.